Test implementation of TQM in china and its impact on business perfromance measures - zhu, huayan (2006)
Today the trend in business is towards globalization and high competition (Ittner, and Larcker. 1998b). Organization need to increase the competition advantages, e.g. reduces costs, develop new products and service, shorten process cycle and response times, and also include worker satisfaction and customer satisfaction. Consumers require high quality and services without concomitant increase in prices (Johnson, 1988; Hayes, 1988). Therefore, organizations seek to develop new management approaches, such as Total Quality Management(TQM). On the other hand, any these new approaches must be linked with a correct performance measures, new management approaches have impact on business performance measures, in terms of "hard" measures and "soft" measures. "Hard"measures always are in the monetary form, like profit; "soft" measures are also called non-financial measures. A variety of performance measurement innovations have been motivated such as from "economic value" measures to "balance scorecards" of integrated financial and non-financial measures: Economic Value Added (Dierk, 1997), and the Balance Scorecard (Kaplan and Norton, 1996). Many literatures have examined the relationship between TQM and business performance measures, such studies as: Ittner and Larcker (1995); Chenhall (1997); Perera et al (1997) and etc. They generally found a positive relationship between TQM and business performance measures.